Students Perception of The Impact of The Merdeka Belajar Kampus Merdeka (MBKM) Program on Improving Graduate Quality at The Faculty of Education, State University of Jakarta - Unifah Rosyidi; Neti Karnati; Rahmatiah; Chyta Anidhyta; Reza Ifnuari; Mohamad Shepna Giantama (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2024)
This research aims to find out that the impact of the MBKM program can contribute to improving the quality of student graduates at FIP ​​UNJ. The research method used is a survey, using a quantitative approach. The data collection technique in this research was carried out using a questionnaire designed in the form of a statement with a Likert assessment, then distributed via Google form involving a sample of 323 FIP UNJ students. The sampling technique of 323 respondents as samples in this study used the technique (Proportional random sampling), namely the sample by paying attention to the proportion of the population elements. The results of this study are that FIP ​​UNJ students tend to have a positive perception of MBKM, which is considered to strengthen experiential learning, improve hard skills and soft skills, and prepare them for the world of work. MBKM contributes significantly to improving the quality of graduates and the suitability between education and work after graduation. This program also supports the development of students' intelligence and personality. However, there are several obstacles in its implementation, such as lack of socialization and cooperation with industry, which can be overcome through increased socialization, cooperation, monitoring, evaluation, and provision of adequate resources to increase the effectiveness of the program.